Studi Long Storage Sebagai Upaya Mengatasi Kekeringan Di Daerah Cinta Manis Sumatera Selatan - Trisdiana, Fitri; Arifaini, Nur; Zakaria, Ahmad (Universitas Lampung, 2021)
This study aims to conduct a long storage study as an effort to overcome drought in the Cinta Manis area, South Sumatra. The research data used is the maximum daily rainfall data from 2009 - 2018 which was obtained from the Palembang Climatological Rain Station. From the research results obtained hydrological analysis data and hydraulic analysis. For hydrological analysis, statistical parameter methods are used to determine the planned rainfall. The results of this method were analyzed in harmony with the Chi Square test and the Smirnov-Kolmogorov test and the distribution type used was the Log Pearson III distribution. To calculate the water holding capacity in long storage, the cumulative storage volume analysis is used to analyze the volume that is bounded by a certain contour, with a simple formula published by the Manual of Sediment Control Dam Construction of the Ministry of Public Works. Based on the research results, it can be seen that the potential for long storage storage obtained from rainwater is 95771.18 m³ and water storage capacity in long storage which is 137334.43 m³ is able to serve 40.87 ha. The water storage capacity in long storage is able to irrigate the sugarcane fields in Rayon 1B and as a storage place for water reserves so that there is no drought when the dry season arrives.Keywords: long storage, rain, analysis